The European Union's Place in United States–China Strategic Competition: How Role Dynamics Drive Brussels Towards Washington - Sebastian Biba (JCMS: Journal of Common Market Studies, 2024)
Against the backdrop of intensifying United States–China strategic competition, the European Union (EU) has recently changed course and moved closer to mirroring US rhetoric and action on China. Why has this happened, and how can it be best explained? In this article, it is argued that current role dynamics between the EU and the two rival great powers can help us understand the growing, albeit not full, EU–United States alignment on China. Role theory assumes that co-operation between actors intensifies when their roles become more compatible. Accordingly, it is shown that the EU has recently adjusted its role to be more closely aligned with the United States' position. That is to say, the EU has reshaped its own role conception, whilst the bloc has likewise become more open to meeting US role expectations after EU–United States role-playing turned positive once again under President Joe Biden.
Keywords: 330; EU foreign policy behaviour; EU–China relations; EU–United States relations; role theory; United States–China competition